2017
DOI: 10.13005/ojc/330413
|View full text |Cite
|
Sign up to set email alerts
|

Production of Macrocyclic Polyether Benzo-15-Crown-5 and its Functional Derivatives

Abstract: Study of interaction between catechol and tetraethylene glycol dichloride in the n-butanol media, resulting with benzo-15-crown-5 production. Production of nitro-and amino-derivatives of benzo-15-crown-5. Determination of their thermogravimetric characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
3
2
0
Order By: Relevance
“…On the other hand, the thermal behavior of 18-crown-6 is not clearly understood with few data available in the literature. The thermogram of 18-crown-6 (Figure e) suggested that the thermal decomposition process of crown ethers is a complicated process, as reported by Glushko et al . The process may occur in two stages: melting endotherm and decomposition exotherm.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…On the other hand, the thermal behavior of 18-crown-6 is not clearly understood with few data available in the literature. The thermogram of 18-crown-6 (Figure e) suggested that the thermal decomposition process of crown ethers is a complicated process, as reported by Glushko et al . The process may occur in two stages: melting endotherm and decomposition exotherm.…”
Section: Resultssupporting
confidence: 65%
“…42 On the other hand, the thermal behavior of 18-crown-6 is not clearly understood with few data available in the literature. The thermogram of 18crown-6 (Figure 7e) suggested that the thermal decomposition process of crown ethers is a complicated process, as reported by Glushko et al 43 The process may occur in two stages: melting endotherm and decomposition exotherm. The endothermic peak of 18-crown-6 melting point cannot be detected in the thermogram as 18-crown-6 melts at low temperature (around 42 °C); 44 however, a sharp exothermic peak, which may correspond to the ignition of 18-crown-6 during its decomposition, is detectable near 275 °C, as reported about other crown ethers in the literature.…”
Section: ■ Results and Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Pyromellitic anhydride (PMDA), dianhydride 3,3', 4,4' -benzophenontetracarboxylic acid (BPDA), dianhydride 3,3', 4,4' -diphenylacetylene acid (FTFA) dianhydride 1,4-bis(3',4'dicarboxyphenoxy)-benzene (GHDFA) and diamino-dibenzocrown-esters were obtained by us earlier 17,18 . Mass fraction of basic substance was more than 97%.…”
Section: Materials and Reagentsmentioning
confidence: 99%